Developing Instagram-Based E-Poster for Learning the Concept of Alkaline Group of Periodic Table - Muhammad Nazar; Ratu Fazlia Inda Rahmayani; Diwana Aida; Kana Puspita (Jurnal Penelitian Pendidikan IPA, 2021)
This research aimed at developing e-poster as learning media, analyzing how students respond to the e-posters uploaded to Instagram. This R&D research utilized an ADDIE model of development consisting of five stages: analysis, design, development, implementation, and evaluation. The research took place during even semester at the Department of Chemical Education, Faculty of Education and Teacher Training, Universitas Syiah Kuala. A total of twenty-four students (4 male and 20 female) who enrolled in the course of "elements and compounds of primary groups" voluntarily took part in the research subjects. We collect the data using the following instruments: A validity assessment form, a questionnaire for students, and an active Instagram account necessary for uploading the contents and monitoring students' activity on the platform.Â  The results show that the validity score of e-posters was 97.5%, and 89 % of students responded positively to the media, and the vast majority of students would prefer to learn using e-posters in the future. The findings indicated that e-posters could contribute as alternative learning media to help students understand the concept of alkali group elements